Perinatal Factors Associated With Neonatal Mortality In Newborn Less Than 1500 - admin, admin (2018)
Objective. To determine the perinatal factors associated to neonatal mortality in newborns with less than 1500 grams at the INMP. Material and Methods. The perinatal factors associated with neonatal mortality were evaluated based on a historic cohort of 1265 deliveries of very low birth weight newborns (VLBW) at the INMP between 2006 and 2010. The statistical analysis included survival analysis with Kaplan-Meir method and the multivariate analysis by Cox Regression. Results. VLBW were 1,5% of all newborns during the period study. The global survival was 60%. After the multivariate analysis, preeclampsia, premature rupture of membranes, vaginal delivery, masculine gender, severe depression, asphyxia, hyaline membrane disease and ventricular hemorragheae were independently and significantly associated with risk for neonatal mortality. Conclusions.An early screening for preeclampsia and an aggressive management of conditions associated to premature rupture of membranes could reduce the frequency and severity of the extreme preterm newborn. Cesaraea section could be better than vaginal delivery for this group. It exist a low ratio cost: efectivity because the severe complications at neonatal period, for that reason it is necessary to propose a different perinatal perspective in the management of these women with emphasis in the prenatal care.